Daclizumab high-yield process in the treatment of relapsing-remitting multiple sclerosis - Preiningerova, Jana Lizrova; Vachova, Marta (Therapeutic advances in neurological disorders, 2017)
Daclizumab is a humanized monoclonal antibody that binds to the α subunit (CD25) of the interleukin-2 receptor and favorably modulates the immune environment in multiple sclerosis (MS). Blockage of CD25, among other effects, causes expansion and enhanced function of regulatory CD56bright natural killer cells, which seems to be the leading mechanism of action in MS. Phase II and III clinical trials have demonstrated that monthly subcutaneous injections of daclizumab high yield process (DAC HYP) 150 mg in patients with relapsing MS led to a significant reduction of annualized relapse rate and decreased number of contrast-enhanced lesions on brain magnetic resonance imaging. Treatment with DAC HYP had efficacy superior to treatment with weekly injections of interferon β1a. This review summarizes the development of and clinical experience with daclizumab in MS.
Keywords: interleukin 2; multiple sclerosis; daclizumab; CD25